A high temperature resistant ceramic polyurethane composite material and preparation method thereof

By preparation high -temperature additives and composite flame retardants in ceramic polyurethane composite materials, the problem of poor flame retardant performance and high temperature resistance of ordinary polyurethane composite materials, and realize the excellent high temperature resistance and flame retardant performance of the materials. Applicable At high temperature environment.

CN119039765BActive Publication Date: 2025-01-28HUAIBEI NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411529256.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Ordinary polyurethane composite materials have poor flame retardant properties, are prone to combustion, and have safety hazards, and are average in high temperature resistance, making it difficult to meet the needs of use in high temperature environments.

Method used

By preparing high -temperature additives and composite flame retardants, participating in the preparation process of ceramic polyurethane composite materials, a specific process steps and raw materials are used to improve the flame retardant performance and high temperature resistance of the material.

Benefits of technology

The excellent high temperature resistance and fire flame retardant capacity of ceramic polyurethane composite materials can be achieved, which can meet the needs of the use of high temperature environments and have a long -term service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039765B_ABST
    Figure CN119039765B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer materials, and discloses a high-temperature resistant ceramic polyurethane composite material and a preparation method thereof. The high-temperature resistant ceramic polyurethane composite material comprises the following raw materials: polytetramethylene ether glycol, a foaming agent, a high-temperature resistant additive, a composite flame retardant, an organic tin catalyst, isophorone diisocyanate, a low-melting-point glass powder, and talcum powder. The invention prepares the high-temperature resistant additive and the composite flame retardant in the preparation process of the ceramic polyurethane composite material, so that the prepared ceramic polyurethane composite material has excellent high-temperature resistance and fire retardant ability, can meet the use requirements in a high-temperature environment, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a high-temperature resistant ceramic polyurethane composite material and a preparation method thereof. Background Art

[0002] Polyurethane material is a polymer containing an urethane structure in the main chain of the polymer. As an important organic polymer material, it has good elasticity, wear resistance, tear resistance and aging resistance. It is known as the "fifth plastic" and is widely used in light industry, chemical industry, construction and other fields. Especially in the construction field, polyurethane foam material is an ideal building insulation material with excellent thermal insulation function. However, ordinary polyurethane materials are not resistant to high temperatures and are easy to burn, which poses great safety hazards when used.

[0003] Ceramic polymer material is a thermal protection composite material. It is a composite material made by adding ceramic fillers, flux and other additives to a polymer matrix and undergoing special processing. It can maintain the mechanical properties and processing properties of general polymer materials at room temperature, and can form a hard ceramic body under flame or high temperature, thereby forming a heat insulation and fireproof effect. The ceramic polymer material formed with polyurethane as the matrix material has better high temperature resistance and fire retardant ability than ordinary polyurethane composite materials. For example, the patent with announcement number CN106349455B discloses a high temperature resistant ceramic polyurethane foam composite material and The preparation method thereof comprises: the high-temperature resistant ceramic polyurethane composite material comprises two components A and B; the two components A and B are mixed, and the obtained mixture is injected into a mold for foaming and forming, so as to obtain a ceramic polyurethane foam composite material; the material has excellent high-temperature resistance and flame retardancy and fireproofing capabilities; however, a mixed inorganic flame retardant composed of expandable graphite, phosphate and zinc borate is used as a flame retardant effective component; the inorganic flame retardant has poor compatibility with a polyurethane organic matrix; in actual use, the inorganic flame retardant may precipitate out of the ceramic polyurethane foam composite material over time, resulting in reduced flame retardancy of the material and causing safety hazards. Summary of the invention

[0004] The purpose of the present invention is to provide a high-temperature resistant ceramic polyurethane composite material and a preparation method thereof, which solves the following technical problems: (1) Ordinary polyurethane composite materials have poor flame retardancy and are easy to burn, posing a safety hazard; (2) Ordinary polyurethane composite materials have general high-temperature resistance and are difficult to meet the use requirements in high-temperature environments.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high temperature resistant ceramic polyurethane composite material comprises the following raw materials in parts by weight: 30-50 parts of polytetramethylene ether glycol, 10-12 parts of foaming agent, 6-8 parts of high temperature resistant additive, 5-6 parts of composite flame retardant, 3-5 parts of organic tin catalyst, 28-32 parts of isophorone diisocyanate, 3-5 parts of low melting point glass powder, and 2-3 parts of talc;

[0007] The high temperature resistant additive is prepared by reacting triazine-modified nitrile rubber with hexamethyldisilazane; the triazine-modified nitrile rubber is prepared by reacting epoxy-terminated nitrile rubber with 3-amino-6-bromo-1,2,4-triazine;

[0008] The composite flame retardant is prepared by the reaction of modified xanthan gum and diethyl hydroxymethylphosphonate; and the modified xanthan gum is prepared by the reaction of xanthan gum and 2-chloro-6-pyridine carboxylate.

[0009] Furthermore, the foaming agent is monofluorodichloroethane; and the organic tin catalyst is any one of dibutyltin dilaurate and stannous octoate.

[0010] Furthermore, the preparation method of the high temperature resistant additive comprises the following steps:

[0011] S1: placing the epoxy-terminated nitrile rubber and 3-amino-6-bromo-1,2,4-triazine in toluene, heating the reaction, and collecting the product after the reaction to obtain the triazine-modified nitrile rubber;

[0012] S2: Place the triazine-modified nitrile rubber in xylene, add hexamethyldisilazane and an accelerator, raise the temperature to 75-80°C for reaction for 5-6 hours, collect the product after reduced pressure distillation, and obtain a high temperature resistant additive.

[0013] In this scheme, the epoxy group in the epoxy-terminated nitrile rubber structure undergoes a ring-opening reaction with the amino group in 3-amino-6-bromo-1,2,4-triazine, and the triazine ring is introduced into the polymer segment of the nitrile rubber to obtain a triazine-modified nitrile rubber. Then, under the action of an accelerator, the active bromine in the triazine-modified nitrile rubber structure undergoes a substitution reaction with the imine group in the hexamethyldisilazane structure to obtain a high-temperature resistant additive. This high temperature resistant additive uses nitrile rubber as a polymer matrix, has excellent toughness, can improve the impact resistance of ceramic polyurethane composite materials, and at both ends of its structure have hydroxyl groups, can participate in the preparation process of ceramic polyurethane composite materials, and has excellent compatibility with the matrix material. The introduced triazine ring structure has a stable chemical structure, is not easy to decompose or degrade at high temperatures, and has more excellent high temperature resistance. At the same time, this high temperature resistant additive also has a silazane structure, and the Si-N bond has high bond energy and is not easy to be destroyed, which can further improve the high temperature resistance of the ceramic polyurethane composite material, so that it can meet the use requirements in high temperature environments and have a long service life.

[0014] Furthermore, in step S1, the temperature of the temperature-raising reaction is 80-90° C. and the time is 6-8 hours.

[0015] Furthermore, in step S2, the accelerator is sodium bicarbonate.

[0016] Furthermore, the preparation method of the composite flame retardant comprises the following steps:

[0017] SS1: Place xanthan gum in deionized water, stir thoroughly, add 2-chloro-6-pyridine carboxylate and potassium carbonate, heat to 60-65°C for reaction for 3-5h, remove the solvent by rotary evaporation, and collect the product to obtain modified xanthan gum;

[0018] SS2: Place the modified xanthan gum in N,N-dimethylformamide, mix and stir thoroughly, add diethyl hydroxymethylphosphonate and a catalyst, heat to 90-100°C and react for 2-3 hours. After the reaction, collect the product to obtain a composite flame retardant.

[0019] In this scheme, under the promotion of potassium carbonate, the hydroxyl group in the xanthan gum structure and the active chlorine in the 2-chloro-6-pyridine carboxylate structure undergo substitution reaction to obtain modified xanthan gum, and then under the action of a catalyst, the carboxyl group in the modified xanthan gum structure reacts with the hydroxyl group in the diethyl hydroxymethyl phosphate structure to obtain a composite flame retardant. This composite flame retardant has good compatibility with the ceramic polyurethane composite matrix, and uses xanthan gum as a carbon source, 2-chloro-6-pyridine carboxylate as a gas source, and hydroxymethyl phosphate as an acid source to form an organic expansion composite flame retardant. Involving it in the preparation process of the ceramic polyurethane composite material can effectively improve the flame retardant properties of the material, generate non-combustible gas when a fire occurs, form a stable high-density carbon layer, isolate oxygen, effectively improve the flame retardant ability of the composite material, and improve the safety of the use of the ceramic polyurethane composite material.

[0020] Furthermore, in step SS1, the molecular weight of the xanthan gum is 3000-8000.

[0021] Furthermore, in step SS2, the catalyst is p-toluenesulfonic acid.

[0022] A method for preparing a high temperature resistant ceramic polyurethane composite material comprises the following steps:

[0023] Step 1, fully mixing polytetramethylene glycol, a foaming agent, a high temperature resistant additive, a composite flame retardant and an organic tin catalyst to obtain component 1;

[0024] Step 2, fully mixing isophorone diisocyanate, low melting point glass powder and talcum powder to obtain component 2;

[0025] Step 3: Stir component 1 and component 2 at a rate of 300-500 r / min for 30-45 minutes, pour into a mold, vulcanize at 80-85° C. for 2-2.5 hours, and vulcanize at room temperature for 30-35 days after demolding to obtain a ceramic polyurethane composite material.

[0026] Beneficial effects of the present invention:

[0027] The present invention prepares high temperature resistant additives and composite flame retardants to participate in the preparation process of ceramic polyurethane composite materials, so that the prepared ceramic polyurethane material has excellent high temperature resistance and fire retardant ability, can meet the use requirements in high temperature environment, and has a long service life.

[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0030] Figure 1 The present invention is a flow chart for preparing the high temperature resistant ceramic polyurethane composite material. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The preparation methods of the high temperature resistant additives and the composite flame retardant in the following examples and comparative examples of the present invention are as follows:

[0033] 1. Preparation of high temperature resistant additives

[0034] S1: 2.4 g of epoxy-terminated nitrile rubber and 1.5 g of 3-amino-6-bromo-1,2,4-triazine were placed in 50 ml of toluene, heated to 80° C. and stirred for reaction for 6 h. After the reaction, the product was collected to obtain triazine-modified nitrile rubber;

[0035] S2: 3 g of triazine-modified nitrile rubber was placed in 60 ml of xylene, 2 g of hexamethyldisilazane and 0.5 g of sodium bicarbonate were added, the temperature was raised to 75°C for reaction for 5 h, and the product was collected after reduced pressure distillation to obtain a high temperature resistant additive.

[0036] The bromine content in triazine-modified nitrile rubber and high-temperature resistant additives was detected by titration. The specific detection method is as follows: take 1g triazine-modified nitrile rubber and 1g high-temperature resistant additive as samples, dilute with 15ml deionized water, add 10ml sodium hypochlorite and shake well, add 5g boric acid, heat in a boiling water bath for 10min, cool to 55℃, add 10ml sodium formate solution with a mass fraction of 22%, continue heating for 3min, cool to room temperature, add 1.8g potassium iodide and 18ml hydrochloric acid solution with a concentration of 6mol / L, mix well, use 0.1mol / L sodium thiosulfate standard solution to titrate until the solution changes color, add 2 drops of starch indicator, continue titrating until the solution changes color, and do a blank test at the same time. Calculate the bromine content in the sample according to the following formula:

[0037]

[0038] Wherein, c is the concentration of sodium thiosulfate solution, mol / L; V is the volume of sodium thiosulfate solution consumed by the sample, ml; V0 is the volume of sodium thiosulfate consumed by the blank, ml; m is the mass of the sample, g; 79.904 is the molar mass of bromide ion, g / mol; 6 is the conversion factor; after calculation, the bromine content in triazine-modified nitrile rubber is 7.4%; the bromine content in the high-temperature resistant additive is 1.7%. Compared with the bromine content in triazine-modified nitrile rubber, the bromine content in the high-temperature resistant additive is significantly reduced, which is due to the substitution reaction between the active bromine in the structure of triazine-modified nitrile rubber and the imine group in the structure of hexamethyldisilazane, resulting in consumption.

[0039] 2. Preparation of composite flame retardant

[0040] SS1: 3.2 g of xanthan gum with a molecular weight of 3000 was placed in 50 ml of deionized water, and after being fully stirred and mixed, 3 g of 2-chloro-6-pyridine carboxylate and 0.2 g of potassium carbonate were added, and the temperature was raised to 60°C for reaction for 3 h. After the solvent was removed by rotary evaporation, the product was collected to obtain modified xanthan gum;

[0041] SS2: Place 3.5 g of modified xanthan gum in 60 ml of N,N-dimethylformamide, mix and stir thoroughly, then add 3 g of diethyl hydroxymethylphosphonate and 0.5 g of p-toluenesulfonic acid, heat to 90°C and react for 2 h. After reaction, collect the product to obtain a composite flame retardant.

[0042] The acid-base titration method was used to test the carboxyl content in modified xanthan gum and composite flame retardant. 1g of modified xanthan gum and composite flame retardant were taken as samples respectively. The samples were placed in 50ml of acetone, and an excess of 0.1mol / L KOH-ethanol standard solution was added. Two drops of phenolphthalein indicator were added, and the mixture was fully mixed and shaken. The solution was titrated with 0.1mol / L hydrochloric acid standard solution until the color disappeared completely. A blank test was performed at the same time. The volume of the consumed hydrochloric acid standard solution was recorded and calculated according to the following formula: Carboxyl content (%) = 0.045 × C (V-V0) × 10 0% / M; where 0.045 is the molar mass of carboxyl, kg / mol; C is the concentration of hydrochloric acid standard solution, mol / L; V is the volume of hydrochloric acid standard solution consumed by the sample, ml; V0 is the volume of hydrochloric acid standard solution consumed in the blank sample, ml; M is the sample mass, g; It is calculated that the content of carboxyl in modified xanthan gum is 8.2%, and the content of carboxyl in the composite flame retardant is 0.7%. Compared with the content of carboxyl in modified xanthan gum, the content of carboxyl in the composite flame retardant is significantly reduced, which is due to the reaction and consumption of carboxyl in the modified xanthan gum structure and hydroxyl in the diethyl hydroxymethylphosphonate structure.

[0043] Example 1

[0044] Preparation of ceramic polyurethane composites

[0045] Step 1: 30 parts of polytetramethylene glycol, 10 parts of monofluorodichloroethane, 6 parts of high temperature resistant additives, 5 parts of composite flame retardant and 3 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0046] Step 2: 28 parts of isophorone diisocyanate, 3 parts of low melting point glass powder and 2 parts of talcum powder are fully mixed and stirred to obtain component 2;

[0047] Step 3: Stir component 1 and component 2 at a rate of 300 r / min for 30 minutes, pour them into a mold, vulcanize them at 80° C. for 2 hours, and vulcanize them at room temperature for 30 days after demolding to obtain a ceramic polyurethane composite material.

[0048] Example 2

[0049] Preparation of ceramic polyurethane composites

[0050] Step 1: 40 parts of polytetramethylene glycol, 11 parts of monofluorodichloroethane, 7 parts of high temperature resistant additives, 5.5 parts of composite flame retardant and 4 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0051] Step 2: 30 parts of isophorone diisocyanate, 4 parts of low melting point glass powder and 2.5 parts of talc are fully mixed and stirred to obtain component 2;

[0052] Step 3: Stir component 1 and component 2 at a rate of 400 r / min for 35 minutes, pour into a mold, vulcanize at 82° C. for 2.2 hours, and vulcanize at room temperature for 32 days after demolding to obtain a ceramic polyurethane composite material.

[0053] Example 3

[0054] Preparation of ceramic polyurethane composites

[0055] Step 1: 50 parts of polytetramethylene glycol, 12 parts of monofluorodichloroethane, 8 parts of high temperature resistant additives, 6 parts of composite flame retardant and 5 parts of stannous octoate are fully mixed to obtain component 1;

[0056] Step 2: 32 parts of isophorone diisocyanate, 5 parts of low melting point glass powder and 3 parts of talcum powder are fully mixed and stirred to obtain component 2;

[0057] Step 3: Stir component 1 and component 2 at a rate of 500 r / min for 45 minutes, pour them into a mold, vulcanize at 85° C. for 2.5 hours, and vulcanize at room temperature for 35 days after demolding to obtain a ceramic polyurethane composite material.

[0058] Comparative Example 1

[0059] Preparation of ceramic polyurethane composites

[0060] Step 1: 40 parts of polytetramethylene glycol, 11 parts of monofluorodichloroethane, 5.5 parts of a composite flame retardant and 4 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0061] Step 2: 30 parts of isophorone diisocyanate, 4 parts of low melting point glass powder and 2.5 parts of talc are fully mixed and stirred to obtain component 2;

[0062] Step 3: Stir component 1 and component 2 at a rate of 400 r / min for 35 minutes, pour into a mold, vulcanize at 82° C. for 2.2 hours, and vulcanize at room temperature for 32 days after demolding to obtain a ceramic polyurethane composite material.

[0063] Comparative Example 2

[0064] Preparation of ceramic polyurethane composites

[0065] Step 1: 40 parts of polytetramethylene glycol, 11 parts of monofluorodichloroethane, 7 parts of high temperature resistant additives and 4 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0066] Step 2: 30 parts of isophorone diisocyanate, 4 parts of low melting point glass powder and 2.5 parts of talc are fully mixed and stirred to obtain component 2;

[0067] Step 3: Stir component 1 and component 2 at a rate of 400 r / min for 35 minutes, pour into a mold, vulcanize at 82° C. for 2.2 hours, and vulcanize at room temperature for 32 days after demolding to obtain a ceramic polyurethane composite material.

[0068] Comparative Example 3

[0069] Preparation of ceramic polyurethane composites

[0070] Step 1, 40 parts of polytetramethylene glycol, 11 parts of monofluorodichloroethane, 7 parts of triazine-modified nitrile rubber, 5.5 parts of composite flame retardant and 4 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0071] Step 2: 30 parts of isophorone diisocyanate, 4 parts of low melting point glass powder and 2.5 parts of talc are fully mixed and stirred to obtain component 2;

[0072] Step 3: Stir component 1 and component 2 at a rate of 400 r / min for 35 minutes, pour into a mold, vulcanize at 82° C. for 2.2 hours, and vulcanize at room temperature for 32 days after demolding to obtain a ceramic polyurethane composite material.

[0073] Comparative Example 4

[0074] Preparation of ceramic polyurethane composites

[0075] Step 1, 40 parts of polytetramethylene glycol, 11 parts of monofluorodichloroethane, 7 parts of epoxy-terminated nitrile rubber, 5.5 parts of composite flame retardant and 4 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0076] Step 2: 30 parts of isophorone diisocyanate, 4 parts of low melting point glass powder and 2.5 parts of talc are fully mixed and stirred to obtain component 2;

[0077] Step 3: Stir component 1 and component 2 at a rate of 400 r / min for 35 minutes, pour into a mold, vulcanize at 82° C. for 2.2 hours, and vulcanize at room temperature for 32 days after demolding to obtain a ceramic polyurethane composite material.

[0078] Comparative Example 5

[0079] Preparation of ceramic polyurethane composites

[0080] Step 1, 40 parts of polytetramethylene glycol, 11 parts of monofluorodichloroethane, 7 parts of high temperature resistant additives, 5.5 parts of diethyl hydroxymethylphosphonate and 4 parts of dibutyltin dilaurate are fully mixed to obtain component 1;

[0081] Step 2: 30 parts of isophorone diisocyanate, 4 parts of low melting point glass powder and 2.5 parts of talc are fully mixed and stirred to obtain component 2;

[0082] Step 3: Stir component 1 and component 2 at a rate of 400 r / min for 35 minutes, pour into a mold, vulcanize at 82° C. for 2.2 hours, and vulcanize at room temperature for 32 days after demolding to obtain a ceramic polyurethane composite material.

[0083] Performance Testing

[0084] The ceramic polyurethane composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were made into samples that met the specifications, and the flame retardant grade of the samples was tested with reference to the UL-94 standard; the tensile strength and elongation at break of the samples were tested using an LJ-500 tensile testing machine; the Vicat softening temperature of the samples was tested with reference to the standard GB / T1633-2000 to determine the high temperature resistance of the samples; the specific test results are shown in the following table:

[0085]

[0086] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent mechanical strength, toughness, high temperature resistance and flame retardancy. The sample prepared in Comparative Example 1 does not contain high temperature resistant additives, and has poor high temperature resistance and toughness, but a composite flame retardant is added thereto, so it has excellent flame retardant effect. The sample prepared in Comparative Example 2 does not contain composite flame retardants, so the flame retardant effect is poor, but high temperature resistant additives are added thereto, so it has excellent high temperature resistance and toughness. The sample prepared in Comparative Example 3 directly adds triazine-modified nitrile rubber and composite flame retardant, and has excellent flame retardant effect, but its high temperature resistance is not as good as that of the example. The sample prepared in Comparative Example 4 directly adds epoxy-terminated nitrile rubber and composite flame retardant, and has good toughness, but average high temperature resistance. The sample prepared in Comparative Example 5 directly adds diethyl hydroxymethylphosphonate and high temperature resistant additives, and has excellent high temperature resistance and toughness, but its flame retardant performance is not as good as that of the example.

[0087] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0088] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A high temperature resistant ceramic polyurethane composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 30-50 parts of polytetramethylene ether glycol, 10-12 parts of foaming agent, 6-8 parts of high temperature resistant additive, 5-6 parts of composite flame retardant, 3-5 parts of organic tin catalyst, 28-32 parts of isophorone diisocyanate, 3-5 parts of low melting point glass powder, and 2-3 parts of talc; The high temperature resistant additive is prepared by reacting triazine-modified nitrile rubber with hexamethyldisilazane; the triazine-modified nitrile rubber is prepared by reacting epoxy-terminated nitrile rubber with 3-amino-6-bromo-1,2,4-triazine; The epoxy group in the epoxy-terminated nitrile rubber structure undergoes a ring-opening reaction with the amino group in 3-amino-6-bromo-1,2,4-triazine, and the triazine ring is introduced into the polymer segment of the nitrile rubber to obtain a triazine-modified nitrile rubber. Then, under the action of an accelerator, the active bromine in the triazine-modified nitrile rubber structure undergoes a substitution reaction with the imine group in the hexamethyldisilazane structure to obtain a high-temperature resistant additive. The composite flame retardant is prepared by reacting modified xanthan gum with diethyl hydroxymethylphosphonate; the modified xanthan gum is prepared by reacting xanthan gum with 2-chloro-6-pyridine carboxylate; Under the promotion of potassium carbonate, the hydroxyl group in the xanthan gum structure and the active chlorine in the 2-chloro-6-carboxylic acid pyridine structure undergo substitution reaction to obtain modified xanthan gum. Then, under the action of a catalyst, the carboxyl group in the modified xanthan gum structure reacts with the hydroxyl group in the hydroxymethyl diethyl phosphate structure to obtain a composite flame retardant.

2. The high temperature resistant ceramic polyurethane composite material according to claim 1, characterized in that: The foaming agent is monofluorodichloroethane; the organic tin catalyst is any one of dibutyltin dilaurate and stannous octoate.

3. The high temperature resistant ceramic polyurethane composite material according to claim 1, characterized in that: The preparation method of the high temperature resistant additive comprises the following steps: S1: placing the epoxy-terminated nitrile rubber and 3-amino-6-bromo-1,2,4-triazine in toluene, heating the reaction, and collecting the product after the reaction to obtain the triazine-modified nitrile rubber; S2: Place the triazine-modified nitrile rubber in xylene, add hexamethyldisilazane and an accelerator, raise the temperature to 75-80°C for reaction for 5-6 hours, collect the product after reduced pressure distillation, and obtain a high temperature resistant additive.

4. The high temperature resistant ceramic polyurethane composite material according to claim 3, characterized in that: In step S1, the temperature of the temperature-raising reaction is 80-90° C. and the time is 6-8 hours.

5. The high temperature resistant ceramic polyurethane composite material according to claim 3, characterized in that: In step S2, the accelerator is sodium bicarbonate.

6. The high temperature resistant ceramic polyurethane composite material according to claim 1, characterized in that: The preparation method of the composite flame retardant comprises the following steps: SS1: Place xanthan gum in deionized water, stir thoroughly, add 2-chloro-6-pyridine carboxylate and potassium carbonate, heat to 60-65°C for reaction for 3-5h, remove the solvent by rotary evaporation, and collect the product to obtain modified xanthan gum; SS2: Place the modified xanthan gum in N,N-dimethylformamide, mix and stir thoroughly, add diethyl hydroxymethylphosphonate and a catalyst, heat to 90-100°C and react for 2-3 hours. After the reaction, collect the product to obtain a composite flame retardant.

7. The high temperature resistant ceramic polyurethane composite material according to claim 6, characterized in that: In step SS1, the molecular weight of the xanthan gum is 3000-8000.

8. The high temperature resistant ceramic polyurethane composite material according to claim 6, characterized in that: In step SS2, the catalyst is p-toluenesulfonic acid.

9. A method for preparing a high temperature resistant ceramic polyurethane composite material as claimed in claim 1, characterized in that: The following steps are involved: Step 1, fully mixing polytetramethylene glycol, a foaming agent, a high temperature resistant additive, a composite flame retardant and an organic tin catalyst to obtain component 1; Step 2, fully mixing isophorone diisocyanate, low melting point glass powder and talcum powder to obtain component 2; Step 3: Stir component 1 and component 2 at a rate of 300-500 r / min for 30-45 minutes, pour into a mold, vulcanize at 80-85° C. for 2-2.5 hours, and vulcanize at room temperature for 30-35 days after demolding to obtain a ceramic polyurethane composite material.

Citation Information

Patent Citations

  • A high-temperature resistant ceramizable polyurethane foam composite material and its preparation method

    CN106349455B

  • High temperature resistant ceramic polyurethane foam composite and preparation method thereof

    CN106349455A

  • Ceramic flame-retardant silicone rubber and preparation method thereof

    CN118772645A